PENGEMBANGAN BAHAN AJAR MODUL BERBASIS KONTEKSTUAL PADA TEMA PEDULI TERHADAP MAKHLUK HIDUP KELAS IV SD - Annisah Putri Hutagalung; Beta Rapita Silalahi (Jurnal Inovasi Penelitian, 2023)
This development research aims to develop contextual-based modules on theme 3 "Caring for Living Things" Sub-theme 1 "Animals and Plants in My Home Environment" that are suitable for use in the learning process in class IV. This research is a type of research and development (Research and Development) using the 4D development procedure developed by Thiagarajan. In this study, researchers carried out the 4D development procedure only up to stage 3, namely development, because the focus of this research was only to develop contextual-based modules on theme 3 "Caring for Living Things" Sub-theme 1 "Animals and Plants in My Home Environment which is suitable for use in the learning process. The instrument used to collect data was a questionnaire or questionnaire given to the validator, namely the media expert validator, material expert validator and learning expert validator. Based on the validation results from the media expert validator, a score of 89.2 was obtained. From the results of the material expert validation, a value of 91 was obtained and from the results of the learning expert validation, a value of 92 was obtained. The average value obtained from the overall assessment of the three expert validators was 90.73. Tracing the scoring score criteria, it can be said that the contextual-based module on theme 3 "Caring for Living Things" Sub-theme 1 "Animals and Plants in My Home Environment" developed is Very Valid for use in the learning process.